1994
DOI: 10.1161/01.atv.14.8.1258
|View full text |Cite
|
Sign up to set email alerts
|

Response to HMG CoA reductase inhibitors in heterozygous familial hypercholesterolemia due to the 10-kb deletion ("French Canadian mutation") of the LDL receptor gene.

Abstract: The 10-kb deletion ("French Canadian mutation") of the low-density lipoprotein (LDL) receptor gene is the most common mutation causing familial hypercholesterolemia among subjects of French Canadian descent. In affected subjects, it results in a null allele of the LDL receptor gene and provides a unique opportunity to examine single-allele regulation of this gene in humans. We sought to ascertain the response of inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase in subjects with the French… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…Hydroxymethylglutaryl coenzyme A (HMG CoA) reductase catalyzes the rate-limiting step in cholesterol synthesis, namely, the conversion of HMG CoA to mevalonic acid (MVA), and its activity is rapidly regulated at the transcriptional, translational, and protein levels. 3 HMG CoA reductase inhibitors (statins) have been very effective in treating FH, but we 4 and others 5,6 have reported large variations in interindividual plasma cholesterol responses to statins, irrespective of the statin and dose used. Whether the nature of the LDL receptor mutation influences the degree of cholesterol lowering achieved by statins is controversial, with evidence for 5,7,8 and against 6,9 -12 this hypothesis.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Hydroxymethylglutaryl coenzyme A (HMG CoA) reductase catalyzes the rate-limiting step in cholesterol synthesis, namely, the conversion of HMG CoA to mevalonic acid (MVA), and its activity is rapidly regulated at the transcriptional, translational, and protein levels. 3 HMG CoA reductase inhibitors (statins) have been very effective in treating FH, but we 4 and others 5,6 have reported large variations in interindividual plasma cholesterol responses to statins, irrespective of the statin and dose used. Whether the nature of the LDL receptor mutation influences the degree of cholesterol lowering achieved by statins is controversial, with evidence for 5,7,8 and against 6,9 -12 this hypothesis.…”
mentioning
confidence: 86%
“…3 HMG CoA reductase inhibitors (statins) have been very effective in treating FH, but we 4 and others 5,6 have reported large variations in interindividual plasma cholesterol responses to statins, irrespective of the statin and dose used. Whether the nature of the LDL receptor mutation influences the degree of cholesterol lowering achieved by statins is controversial, with evidence for 5,7,8 and against 6,9 -12 this hypothesis.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We conclude from these data that LCO-TyrGalNAc 3 is very effective in promoting cholesterol transport to hepatocytes and, thus, may be a promising alternative for hyperlipidemic individuals who do not respond sufficiently to current cholesterol-lowering therapies, such as familial hypercholesterolemic patients. 20,21 …”
mentioning
confidence: 99%
“…HMG-CoA reductase inhibitors decrease plasma concentration and urinary excretion of MVA (23). Findings in familial hypercholesterolemia volunteers in South Africa treated with high doses of atorvastatin, simvastatin, or pravastatin showed that, compared with good responders, poor responders had a lower basal level and a smaller decrease of plasma MVA on statins (24). Marked reductions in plasma and urine MVA following rosuvastatin treatment for 14 days were observed (25).…”
Section: Estimation Of Serum Mvamentioning
confidence: 99%